Unsur sinkretisme dalam uruf dan adat masyarakat Bajau di Sabah: Analisis dari perspektif hukum Islam / Syamsul Azizul Marinsah - Syamsul Azizul, Marinsah (2017)
Every society has its own culture through interactions with various civilizations and religions, in synergy with various elements of syncretism. Through the efforts of local scholars that assimilate the traditional culture with Islamic sharia, multiple patterns of local wisdoms were emerged. However, through the interaction as well, two practices arise; ‘urf sahih which is accepted by Syarak, and ‘urf fasid which is polluted by the elements of forbidden bidaah, superstition and khurafat. In the Bajau community, the traditional practices have gone through the process of harmonization with Islamic teachings. Despite that, there is still a tendency towards the remnants of pre-Islamic beliefs in the form of superstition. Hence, the objective of this study is to explain the syncretism phenomena that exist in the custom and common practices of the Bajau community in Sabah, particularly in Semporna and Kota Belud. The researcher focuses on the aspects of traditional beliefs, child birth custom, marriage custom as well as the custom surrounding death. These customs will be analyzed through an Islamic perspective to examine whether they comply with Syarak or vice versa. This qualitative research applies literature review together with fieldwork in achieving its objectives. Data collection is done using methods which include documentation, interview as well as observation. To sum up the findings, all data collected will be inductively, deductively and comparatively analyzed. The study found that there are elements of syncretism in the ‘urf and customs of Bajau community in all the four main aspects of research. However, not all of them are fasid, forbidden bidaah, superstitious or khurafat. In fact, some of the practices even arise from the local wisdom; for example, the usage of coconut milk in the process of bathing the body of the deceased. Coconut milk which is more commonly used in cooking is used as cleaning agent to soften the joints of the body. Based on the findings, a clear parameter of syncretism which obeys the Sharia was developed as a guideline to Islamic community to ensure customary practices are in line with the Syarak.